UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI PENGGUNAAN METODE POSTER COMMENT PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SD INPRES PAJAGALUNG - selvi; Muhammad Akhir; Amal Akbar (STKIP Subang, 2025)
This study aims to improve students’ critical thinking skills through the use of the Poster Comment method in the Indonesian language subject for fifth-grade students at SD Inpres Pajagalung. The Poster Comment method is a learning approach that encourages students to actively provide responses to posters containing specific information or issues, thereby stimulating their critical and analytical thinking abilities. This research employed a classroom action research (CAR) approach with two cycles, each consisting of planning, implementation, observation, and reflection. The research subjects were fifth-grade students at SD Inpres Pajagalung. The results showed an improvement in students’ critical thinking skills from the first cycle to the second cycle. This improvement was evident from the increase in the average scores and the percentage of students achieving mastery learning after the implementation of the Poster Comment method. Therefore, it can be concluded that the Poster Comment method is effective in enhancing students’ critical thinking skills in Indonesian language learning.